Evaluation of dose dependent analgesic response by extracts of Myristica fragrans on albino wistar rats: an experimental study - Zaheer, Imran; Rahman, Syed Ziaur; Khan, Rahat Ali; Parveen, Mehtab; Sharma, Priyamvada (International Journal of Basic & Clinical Pharmacology, 2019)
Background: The objective of the study was to evaluate analgesic activity of ethanolic extract, methanol and benzene fraction of Myristica fragrans on wistar albino rats. Methods: The present study was carried out in the department of pharmacology JNMC AMU and F.H. Medical College, Agra. The analgesic activity was evaluated by employing the Eddy’s hot plate method and tail flick response method. In both the tests, Rats of either sex weighing 150-200 g were used. The total number of animals n=36 were allocated to six groups. Each group consist of six animals each. The response noted in animals that were tested by hot plate method was reaction time for licking/biting of both the paws before and after administration of control & test drugs. However in Tail flick test, the pain threshold response was recorded before and after administration of control & test drugs. The statistical analysis was done by using one-way ANOVA. The data is expressed as Mean±SEM. P<0.05 was considered to be statistically significant. Results: Ethanolic extracts and methanol fraction of M. fragrans showed statistically significant (p<0.001) increase in reaction time for licking/biting in hot plate method. On the contrary a significant increase in pain threshold was also recorded in tail flick response test. It is interesting to note that no significant degree of analgesia related to any dose of benzene fraction was observed. Conclusions: The present study reveals the dose dependent significant analgesic activity of the extracts of M. fragrans i.e. ethanolic extracts and methanol fraction in both the test. However, the degree of analgesia was recorded significantly higher in groups received higher doses of extracts of M. fragrans.